Middle Ear Pressure and Factors Affecting It in Intubated Patients Hospitalized in Intensive Care - Mehmet Akdağ; Müzeyyen Çetin; Zeynep Yıldırım Baysal; Ali Kemal Kadiroğlu; Mehmet Yusuf Çelik; Faruk Meriç (Turkish Archives of Otorhinolaryngology, 2014)

(untitled)
Objective:To assess the probable agents affecting middle ear pressure in intubated patients hospitalized in intensive care units with various diagnoses.Methods:Middle ear pressure of 38 patients hospitalized in intensive care units within our faculty hospital was measured using portable tympanograms and acoustic reflectometry. The mode of the device to which each patient was attached and patients’ blood pressure, Glasgow Coma Score, and additional disease parameters other than admission diagnosis were recorded. All data collected were subjected to statistical analysis to determine whether or not they affected middle ear pressure.Results:Septal deviation, survey, and mode of automatic respiratory device emerged as factors affecting middle ear pressure (odds coefficient 4.796, 3.745, 2.557, respectively, with 95% CI). Although aged over 60, additional disease and nasogastric tube also compromised middle ear pressure; the levels involved were not statistically significant.Conclusion:Middle ear pressure in patients hospitalized in intensive care units may change, particularly after the seventh day. This may particularly involve septal deviation, survey, and mode of automatic respiratory device, and tympanograms and reflectometry may be added to the patient-monitoring protocol in terms of changes in middle ear pressure.